Evolution of pore structure during fines migration in sand pack: NMR experimental and numerical investigations - Haoxuan, Tang; Chunsheng, Jia; Ziyi, Wang; Hao, Lu; Zhao, Wang; Hongming, Tang; Baiyu, Zhu (Frontiers in Energy Research, 2024)
Unconsolidated sand reservoirs containing heavy oil play a significant role in hydrocarbon resources, characterized by high porosity and permeability alongside abundant movable fines. During production, these fines can detach and migrate with the reservoir fluids, causing pore plugging and reduced productivity. Visualizing and quantitatively evaluating the evolution of pore structure caused by fines migration under various influencing factors at the microscale is fundamental for devising effective prevention and mitigation measures.This study employs on-line NMR experiments and CFD-DEM simulations to investigate fines migration processes and their effects on physical properties and pore structure at the pore scale. Results indicate that fines migration initiates the formation of a preferential network of migration pathways.The evolution of pore structure demonstrates zonal characteristics along the flow direction, with fines plugging and residual accumulation primarily occurring in the middle/rear section of the core. As the core's skeleton porosity decreases, fines plugging intensifies; however, at high injection velocity, new dominant flow channels may emerge, leading to a transition from a single-peak to a double-peak T2 spectrum. Below the critical velocity (0.5-1 mL/min), an increase in flow velocity exacerbates severe fines plugging. Conversely, above the critical velocity, an increase in flow velocity results in a more pronounced enhancement of permeability.